Stress-Affected Oxygen Reduction Reaction Rates on UNS S13800 Stainless Steel - Hangarter, Carlos M.; Anderson, Rachel M.; Policastro, Steven A. (Frontiers in Chemistry, 2022)
This work investigates the previously unexplored impact of tensile stress on oxygen reduction reaction (ORR) kinetics of a precipitation-hardened, stainless-steel fastener material, UNS S13800. ORR is known to drive localized and galvanic corrosion in aircraft assemblies and greater understanding of this reaction on structural alloys is important in forecasting component lifetime and service requirements. The mechano-electrochemical behavior of UNSS13800 was examined using amperometry to measure the reduction current response to tensile stress. Mechanical load cycles within the elastic regime demonstrated reversible electrochemical current shifts under chloride electrolyte droplets that exhibited a clear potential dependence. Strain ramping produced current peaks with a strain rate dependence, which was distinct from the chronoamperometric shifts during static tensile load conditions. Finally, mechanistic insight into the dynamic and static responses was obtained by deoxygenation, which demonstrated ORR contributions that were distinct from other reductive processes.